Enhancing oligodendrocytes generation and myelin renewal by vitamin C mitigate Parkinson-relevant phenotypes in a murine model of Parkinson’s disease - Cui, Shihao; Wang, Shengyuan; Liu, Min; Zou, Qian; Cai, Zhiyou; Ma, Jingxi (Frontiers in Cellular Neuroscience, 2026)
Parkinson’s disease (PD) is a major neurodegenerative disease with an increasing global prevalence. In addition to progressive dopaminergic neurons degeneration, emerging evidence implicates oligodendrocyte (OL) dysfunction and impaired myelin also contribute to PD pathogenesis. Here, we observed a significant reduction of myelin basic protein (MBP) and the number of OLs in the MPTP-induced chronic PD mouse model. Vitamin C (VC) has been reported to promote myelin regeneration in the demyelination mouse model, though its underlying mechanism remains unclear. Therefore, this study investigated the therapeutic effects of VC in the mouse model of PD by the enhancement of OPC-to-oligodendrocyte differentiation and myelin renewal. Using in vitro oligodendrocyte precursor cell (OPC) differentiation systems, we confirmed that VC markedly enhanced the differentiation of OPC to OL. In MPTP-induced PD mice, VC treatment not only ameliorated myelin damage but also protected dopaminergic neurons, and led to a significant improvement in PD-relevant behavioral phenotype. Mechanistically, the effects of VC are mediated through the activation of Ten-eleven translocation (TET) enzymes, which promotes DNA hydroxymethylation and subsequent expression of genes essential for OL differentiation. Taken together, these findings suggest that promoting OPC-to-oligodendrocyte differentiation and myelin repair by VC could serve as a promising therapeutic strategy in PD.